(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
When talking about the use of the native language in the enrichment of terminology, it is necessary to pay attention to the following three points: 1. In a particular language, as well as in Uzbek, a number of lexemes have been used since ancient times to express the concepts of a field.